Desenvolvimento e avaliação do papel biológico de peptídeos inibidores de activina a em células pulmonares - Bastos, Victor Alexandre Félix (2020)
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and fibrous interstitial pneumonia, of unknown cause, limited to the lungs, that mostly affects the elderly. Its progressive character limits patients' survival to about three to five years. Current treatments, despite slowing its progression, are not able to prevent the disease progress or reverse its effects. Activin A plays a fundamental role in the development of IPF, being mainly responsible for the transformation of fibroblasts into myofibroblasts at the site of the lung injury. This study sought to inhibit the action of activin A through the use of synthetic peptides, capable of binding and neutralizing the action of activin A. Selection of peptides by phage display made it possible to select ten unique peptides that are able of binding to activin A. After evaluation of the binding potential, three peptides (A7, B9, and E10) were chosen to have their sequences synthesized. Structural evaluation in silico of the peptides, as well as their interaction with an activin A molecule, demonstrated that the peptide-protein binding points are located in the same region used for the binding of activin A with its cell receptor (ActRIIB). In addition, cell migration assays demonstrated the ability of peptides to decrease lung cell proliferation, even when stimulated with pmTGF-β. The synthetic peptide E10 was also capable of inhibiting an epithelial-mesenchymal transition in A549 cells stimulated with pmTFG-β, as well as inhibiting the transformation of fibroblasts into myofibroblasts in vitro. We thus demonstrate the inhibitory potential of a specific synthetic peptide binding for activin A. However, in vivo studies must be conducted to understand the effects of inhibition of activin A and its impact on the progression of IPF.